Enteric Opportunistic Parasitic Infections Among HIVSeropositive Patients in Kathmandu, Nepal - Sherchan, JB; Ohara, H; Sakurada, S; Basnet, A; Tandukar, S; Sherchand, JB; Bam, DS (Kathmandu University Medical Journal, 2013)
Background Enteric opportunistic parasitic infections are the major source of diarrheal disease in developing countries mainly in Human Immunodeficiency virus (HIV) infected patients. Objective The study was to detect enteric parasites causing diarrhea and their association with immune status in HIV-seropositive patients. Methods The present study was conducted in Dirgh-Jeevan Health Care Research Center and Tribhuvan University Teaching Hospital, Public Health Research Laboratory, Kathmandu, Nepal between June 2010 and May 2011 involving 146 Human Immunodeficiency virus (HIV) positive patients. Serostatus from these patients were detected by Enzyme Linked Immunosorbent assay. CD4+ T cell counts were done by flow cytometry. Stool was examined for enteric parasites by microscopy with special staining methods. Results A total of 146 HIV sero-positive patients with and without diarrhea age between 20 to 45 years were included in the study. Of the 146 patients, the protozoan parasitic infection was found in 30.13% (44/146). Out of 146 patients, 78 had diarrhea in which parasitic infection was 39 (50%) and 7.35% (5/68) protozoal parasites positive cases did not have diarrhea. A significant difference (p<0.05) was observed in the level of infection of intestinal protozoan between the HIV seropositive with diarrhea and HIV-seropositive without diarrhea. Out of 43 patients whose CD4+ T cells were <200/?l, 29 (67.4%) had opportunistic parasitic infection whereas out of 103 patients whose CD4+ T cells were ?200/?l, only 15 (14.56%) had opportunistic parasitic infection (P < 0.05). Conclusion Enteric opportunistic parasitic infections were detected in 30.1% among HIV-seropositive patients and low CD4+ T count indicated high enteric opportunistic infection. Early detection of enteric parasitic infections will help in the management and to improve the quality of life for HIV-infected individuals. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 14-17 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7336